Pengaruh Tegakan Mahoni dan Jati terhadap Pertumbuhan dan Hasil Tiga Varietas Kacang Hijau (Vigna radiata L.) pada Sistem Agroforestri - Cicik Udayana; Nunun Barunawati; Anggarina Dian Pramesti (Jurnal Galung Tropika, 2025)
Mung bean production in Indonesia has experienced a decline was caused by the decline in agricultural land area. The planting area in Indonesia for mung bean in 2017 was 206.832 ha, then it decreased to 189.298 ha in 2021. The agroforestry planting pattern is an effort to increase mung bean production, which has decreased due to the reduction in agricultural land area. The aims of this research are to test the growth and yield of three varieties of mung bean that are suitable for planting under mahogany and teak stands using an agroforestry system. The research used combined randomized block design (RBD) Nested Design consisted of 2 treatments, namely types of stands (mahogany and teak stands) and mung bean varieties (Vima 5, Vimil 2, and Kutilang). The results showed that the dry weight of seeds of the varieties of Vima 5 (2.60 ku ha-1), Vimil 2 (1.69 ku ha-1), and Kutilang (2.54 ku ha-1) planted under teak stands had higher yield than under mahogany stands.